The diffusion of small-scale irrigation technologies in Ethiopia: stakeholder analysis using Net-Map - Bryan, Elizabeth; Hagos, Fitsum; Mekonnen, Dawit Kelemework; Gemeda, Demie Abera; Yimam, Seid (International Food Policy Research Institute, 2020)
Small-scale irrigation (SSI) provides great benefits to farmers in terms of increased yields and profits, better food and nutrition security and greater resilience to climate shocks. Ethiopia has high potential for expanding SSI and has invested considerably in this area in recent years. Despite these investments, several challenges to further expansion of irrigation technologies remain. Different stakeholders in the country play important roles in overcoming these barriers to further scale technologies for SSI. This paper explores institutional arrangements for the diffusion of small-scale irrigation technologies by mapping the landscape of key actors involved, their interconnections, and their influence. This paper draws on an analysis of stakeholder data collected through two participatory workshops in Ethiopia, one at the national level and one at the Oromia regional level, using the Net-Map approach. Results show the dominance of government actors in the diffusion of SSI at both the national and regional levels, while most private sector and NGO actors remain in the periphery. Participants in both workshops highlighted the need for increased financing services to support the adoption of SSI and measures aimed at increasing the supply of high-quality irrigation equipment, such as modern water lifting technologies. One notable difference between the national and regional results was that at the regional level, farmers, and to some extent traders and input suppliers, were considered to be more influential in the diffusion of irrigation technologies, while they were considered marginal actors at the national level.